Economic Growth : The Path to the Alleviation of Debt and Poverty - Clausen, A. W. (World Bank, Washington, DC, 2017)
In this speech by A. W. Clausen, President of the World Bank and International Finance Corporation, he reconfirms the Bank's commitment to do all that it can to help the middle-income member countries with severe debt problems to regain sustained, noninflationary economic growth with social progress. Clausen reviewed the course of the debt crisis and the austerity responses of the heavily indebted middle income countries that were unavoidably painful--very sharp cutbacks in imports, reductions in public expenditure programs, depressed domestic income levels. Although most heavily-indebted countries took steps to attract resources into export-oriented industries in order to enhance their future debt-servicing capacity, such measures were in many instances hampered by severe restrictions on imports necessary to effect a quick reduction in the current account deficit. Additional capital is clearly needed to support productive investment. Industrialized countries must maintain steady growth and move to enhance market access for goods and services from developing countries. Developing countries need to adopt export-oriented trade policy, encourage domestic savings, and improve the quality of investments. The Bank will assist with formulation of growth programs, provide expanded capital, and mobilize capital from other sources.